The 6-float wave energy converter M4: Ocean basin tests giving capture width, response and energy yield for several sites. (April 2019) - Carpintero Moreno, Efrain; Stansby, Peter
Abstract: The M4 wave energy converter originally consisted of three in-line floats increasing in diameter (and draft) from bow to stern so that the device heads naturally into the wave direction with power take off (PTO) from a hinge above the mid float. Linear diffraction modelling was found to make quite accurate predictions of power and response. Time domain modelling was extended to a larger number of floats, up to eight with four PTOs, by Stansby et al. (2017). This showed that capacities similar to wind turbines were possible for some sites. Experimental comparison is presented here for a six-float system with two PTOs. For irregular uni-directional waves with JONSWAP spectra measured power was a little larger than that modelled with maximum capture widths greater than one wave length for energy period. Results for angular motion at the PTOs and mooring forces are presented. Wave conditions with different spectral peakedness and multi-directional spreading are applied and energy yield with electricity cost estimates made for 11 offshore sites. Without PTO to give worst case response, results are presented for angular motion and mooring force variation with significant wave height up to extreme values for different peak periods. Angular motion is predominantly linear but mooring force is more complex with largest values in extreme waves occurring in the range of periods for operational conditions. Highlights: Ocean basin testing of the 6-float wave energy converter M4 has been undertaken. Linear diffraction modelling slightly underestimates power conversion. Maximum capture width is greater than one wavelength of energy period. Sensitivity of power conversion to spectral wave conditions is assessed. Energy yields and device capacity for various sites are estimated.